Knowledge, attitudes, and prevalence of vitamin C intake among the general population of the UAE during the COVID-19 pandemic - Saeed, Balsam Qubais; Al Janaahi, Ali; Pinheiro, Ashmita; Al Shamsi, Aisha; Alhaj, Shaikha Salah; Adrees, Ahmad Omar; Al Maeeni, Hind; Darwish, Razan; Hammad, Ahmed; Jamal, Noor Sarchanar; Al Awaad, Mahmood Haitham (Frontiers in Public Health, 2025)
BackgroundThe extent of vitamin C (VC) deficiency and the general intake of this vitamin among the population is currently unknown. Therefore, in this study, we aimed to evaluate the knowledge, attitudes, and prevalence of vitamin C intake among the general population in the United Arab Emirates (UAE).MethodsA cross-sectional study was conducted between February and March 2022 among adults aged 18 years and above residing in the UAE. Participants were recruited through an online platform using a voluntary response sampling approach. Data were collected using a pre-designed, self-administered, 22-item questionnaire available. It assessed four domains: demographics, knowledge, practices, and attitudes related to vitamin C consumption. Data were analyzed using SPSS version 26. Descriptive statistics were computed, and chi-square tests were used to evaluate associations between demographic factors and knowledge levels. A p-value of < 0.05 was considered statistically significant.ResultsAmong 720 participants, 86.1% were female, and 75.6% were aged 18–29. Despite 88.2% reporting VC consumption, only 30.1% demonstrated adequate knowledge, with significant age-related differences (p = 0.015). Younger participants had significantly higher knowledge scores than other age groups. During the COVID-19 pandemic, 53.5% of previous non-consumers began using VC. Attitudes varied 85.8% believed VC aids COVID-19 recovery, 45.7% thought it prevents infection, and 81.9% acknowledged the potential harm from overconsumption. Pandemic-related health concerns significantly increased VC intake (p < 0.001).ConclusionThere is a clear need for evidence-based public health strategies to improve awareness and safe practices related to vitamin C consumption in the UAE. Educational interventions delivered through healthcare professionals, especially pharmacists, and supported by media campaigns should aim to correct misconceptions, promote appropriate use, and prevent potential misuse of vitamin C during public health crises.